PENERAPAN MODEL PEMBELAJARAN KLASIKAL BACA SIMAK METODE UMMI DALAM MENINGKATKAN PEMAHAMAN DAN KEMAMPUAN MEMBACA AL-QUR’AN SANTRI - Moh. Ulum; Wilda Muyassiroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the implementation of the classical read-listen learning model based on the Ummi method in enhancing the Qur'anic reading and writing skills of students in grades VII to IX at Pondok Pesantren Nurul Jadid, Al-Mawaddah Region. The research is motivated by the pesantren’s need for a systematic and effective Qur'anic learning method. The Ummi method adopts a direct approach, repetition, and sincere affection, applied through a classical read-listen model conducted simultaneously at the same time and place under the teacher’s guidance. This research employs a qualitative approach with a case study design, utilizing data collection techniques such as interviews, observations, and documentation, with data validation carried out through triangulation. The findings indicate that the Ummi method can improve the accuracy of makhraj (articulation), the application of tajwid rules, and the correct writing of Arabic lafadz, and it can also serve as a reference for teachers in evaluating and refining Qur'anic literacy instruction strategie